Inflasi pada Fenomena Sosial Ekonomi: Menurut Al-Maqrizi - Pangiuk, Ambok (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2013)
This article explains the reason of inflation based from al-Maqriziâs thought. One of the reasons of inflation according to al Maqrizi is the span of time and space from the source of inflation, concepts of reason which able to grow and protect society, is a necessity to deflect inflation. The most important reason of al-Maqrizi on inflation allows different conventional inflation could happen simultaneously. Islam as a guidance in order to achieve the objective of it categories of the cause inflation according to al-Maqrizi divided into several types based on certain features as the implications of an essential economic-socio phenomenon. Keywords: inflasi, natural inflasi, unnatural inflasi.